Nuclear-structure studies of exotic nuclei with MINIBALL. (9th March 2017) - Butler, P A; Cederkall, J; Reiter, P
Abstract: High-resolution γ -ray spectroscopy has been established at ISOLDE for nuclear-structure and nuclear-reaction studies with reaccelerated radioactive ion beams provided by the REX-ISOLDE facility. The MINIBALL spectrometer comprises 24 six-fold segmented, encapsulated high-purity germanium crystals. It was specially designed for highest γ -ray detection efficiency which is advantageous for low-intensity radioactive ion beams. The MINIBALL array has been used in numerous Coulomb-excitation and transfer-reaction experiments with exotic ion beams of energies up to 3 MeV A –1 . The physics case covers a wide range of topics which are addressed with beams ranging from neutron-rich magnesium isotopes up to heavy radium isotopes. In the future the HIE-ISOLDE will allow the in-beam γ -ray spectroscopy program to proceed with higher secondary-beam intensity, higher beam energy and better beam quality.